Examining the Escalation of Cybercrimes Against Women and Children in India: A Critical Analysis of the COVID-19 Period (2019-2021) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In the face of an ever-evolving digital landscape, cybercrimes have emerged as a pervasive threat, encompassing offenses committed using computers, the internet, and electronic technologies. Despite the enactment of the Information Technology Act in 2000, designed to define and safeguard citizens against virtual criminals, the incidence of cybercrimes in India has not abated. This research paper delves into the alarming escalation of cybercrimes against women and children, a demography particularly vulnerable in the digital sphere, during the critical period of the COVID-19 pandemic (2019-2021). This study examines state-wise data on cybercrimes against women and children, categorizing their types, prevalence, and rates of chargesheet filings and convictions. It also explores the complex factors behind the rising cybercrime rates and the stark contrast with India's low conviction rates.